2022
DOI: 10.1111/jerd.12936
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between connective tissue graft and xenogeneic acellular dermal matrix to treat single gingival recession: A data reanalysis of randomized clinical trials

Abstract: Objectives There are few studies comparing xenogeneic acellular dermal matrixes (XDMs) with connective tissue graft (CTG) to treat single gingival recession (GR). The present study involved a reanalysis of previous studies and comparison of CTG or XDM to treat single RT1/GR. Materials and methods Fifty patients from three previous randomized clinical trials treated either by CTG (n = 25) or XDM (n = 25) were evaluated after 6‐month. Clinical, patient‐centered, and esthetic parameters were assessed. Pearson's c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In several root coverage procedures, a coronally advanced flap with a subepithelial connective tissue graft is considered the gold standard [ 11 , 13 ]. In addition, alternatives such as acellular dermal matrix and collagen matrix are used with a coronally advanced flap to reduce morbidity at the donor site [ 27 , 28 , 29 ]. Although some clinical advantages have been reported, this procedure is not as effective as a coronally advanced flap with a subepithelial connective tissue graft [ 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In several root coverage procedures, a coronally advanced flap with a subepithelial connective tissue graft is considered the gold standard [ 11 , 13 ]. In addition, alternatives such as acellular dermal matrix and collagen matrix are used with a coronally advanced flap to reduce morbidity at the donor site [ 27 , 28 , 29 ]. Although some clinical advantages have been reported, this procedure is not as effective as a coronally advanced flap with a subepithelial connective tissue graft [ 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though direct comparisons cannot be made, when the results of the present study are compared to other studies that evaluated the XDMs to treat GR with intact tooth surface (without NCCL), similar results are observed. Miguel et al 40 showed that CAF+CTG was superior to CAF+XDM for treating single GRs. Pietruska et al 41 also observed superior results for CTG compared to XDM when multiple recessions were treated and the modified coronally advanced tunnel technique was applied in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Even though direct comparisons cannot be made, when the results of the present study are compared to other studies that evaluated the XDMs to treat GR with intact tooth surface (without NCCL), similar results are observed. Miguel et al 40 . showed that CAF+CTG was superior to CAF+XDM for treating single GRs.…”
Section: Discussionmentioning
confidence: 99%